Student Expectations vs. Outcomes: A Mega-Event Learning Experience - Buenano, Andrea; Stacy Warner,; Rachel Madsen, (Experiential Learning and Teaching in Higher Education, 2025)
Professional development and experiential learning opportunities are essential to student success in sport management programs. This work utilizes qualitative content analysis of survey responses to compare students’ expectations regarding a learning opportunity at Super Bowl LVII to students’ reported outcomes after the event. Open-ended data from an online survey prior to the event experience (n =82 students) was analyzed and then compared to data (n=81 students) after the event. Three common themes emerged regarding students’ expectations for the upcoming experience: Networking Experiences, Professional Development, and Mega-Event Experience. The same themes were also reported as post-event experience outcomes. Unexpectedly, Community of Practice emerged as a post-event experience theme. The results illustrated that some of the students’ expectations lined up with their reported outcomes. However, the emergence of Community of Practice reported post-event is noteworthy. Practical implications to enhance and maximize learning through a large sporting event experience are provided.